An App-Based Workplace Mindfulness Intervention, and Its Effects Over Time - Lu, Yizhen; Remond, Julien; Bunting, Michael; Ilies, Remus; Tripathi, Neha; Narayanan, Jayanth (Frontiers in Psychology, 2021)
We investigated the week-to-week effects of a mindfulness intervention on emotional exhaustion, work engagement and job satisfaction in a field study involving 218 participants who participated and reported their weekly outcomes during the 8-week program. To examine how mindfulness impacted work outcomes, we used intra-individual modelling of the eight-week data. Mindfulness increased over time, and time also had indirect effects on emotional exhaustion, work engagement and job satisfaction, through mindfulness. Supplementary growth curve analyses on the improvement of mindfulness over time showed a slight decrease in the positive effect of time on mindfulness.